Gender, Health, and Medicine in Latin America - Introduction - Pieper Mooney, Jadwiga E.; Potthast, Barbara (Anuario de Historia de América Latina, 2023)
This dossier contains six articles on "Gender, Health, and Medicine in Latin America." Contributions thus provide new insights on the complexities of gendered health practices, medicine, and public health.